Old English glossed psalters - Pulsiano, Phillip, 1955-2000 (Toronto Old English series ;, 2001)
The first of three volumes, this book is an edition of forty psalters written or owned in Anglo-Saxon England, half of which are glossed in Old English. The work is an invaluable tool for comparative gloss scholarship, for the study of the influence of vocabulary, the interpretation of glosses, the study of relations among psalters, and the study of the Latin text of the psalms in Anglo-Saxon England. It also presents new insights on the development of centres of learning and the impact of the psalter on literary tradition. Each volume addresses a group of fifty psalms.This landmark in Old English studies is the first attempt at a completely comprehensive edition. As an original and much-needed contribution to early medieval scholarship, it not only provides a standard edition of texts based on all known Anglo-Saxon psalters but also synthesizes many studies of psalter scholarship from the earliest times.